Analisis Kebutuhan Penguatan Psychological Adjustment Warga Binaan Perempuan dalam Perspektif Bimbingan dan Konseling - Ayu, Siska Putri; Zahrani, Sarah Shafa; Umar, Nur Fadilah; Wibowo, Dwi Endrasto (FKIP Universitas Islam Jember, 2025)
This study aims to describe the need assessment of psychological adjustment among female inmates at the Women’s Penitentiary in “X” Regency. The research background highlights the psychological vulnerability of female inmates who often experience emotional distress due to loss of freedom, limited social interaction, and negative societal stigma. This study used is descriptive qualitative with data sources in the form of needs assessment results, interviews, and field observations. The analysis revealed that 70% of inmates experienced stress due to a new and restrictive environment, 80% felt pressured by social stigma, and 70% were anxious about being rejected by society after release. These findings indicate a high level for strengthening psychological adjustment, particularly in managing stress, developing self-acceptance, and enhancing social support. The study underscores the importance of establishing community-based counseling services to promote psychological well-being and facilitate social reintegration for female inmates. This study provides context-specific evidence for designing community-based counseling interventions in female correctional institutions, which has received limited empirical attention in Indonesia.